1996
DOI: 10.1177/105268469600600605
|View full text |Cite
|
Sign up to set email alerts
|

New Principals in an Urban Bureaucracy: A Sense of Efficacy

Abstract: As principals assume their roles in an urban bureaucracy, what are some of the personal and organizational factors that support or restrict their efforts to bring about school change? Based on interviews with newly appointed principals, this study concludes that external and internal factors interact to influence leadership behavior. External factors, particularly role models, district expectations, and personal and organizational support, influence principals’ sense of self-efficacy. This internal factor, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 17 publications
1
19
0
2
Order By: Relevance
“…Apart from the influence of the principal preparation programme (Holligan et al 2006), gender discrimination (Dunshea 1998) and the NP's professional biography (Sleegers et al 2009), much significance has been attributed to the support and guidance NPs receive in their work for their career development and professional socialization. It was found that NPs receive support from a wide variety of sources, including their district, peers, staff, administrative team, professional networks, governors, parents, family, community, role models, friends and even the former principal of the NP when the NP was a teacher , Osterman and Sullivan 1996, Cheung and Walker 2006, Crow 2007, Kelly and Saunders 2010. Clear district expectations and goals, technical help from supervisors or senior team managements, the capacity of the staff to handle change and mentoring are examples of the type of support given to newly appointed principals.…”
Section: Determinants Affecting the Early Career Stage Of Principalshipmentioning
confidence: 98%
See 2 more Smart Citations
“…Apart from the influence of the principal preparation programme (Holligan et al 2006), gender discrimination (Dunshea 1998) and the NP's professional biography (Sleegers et al 2009), much significance has been attributed to the support and guidance NPs receive in their work for their career development and professional socialization. It was found that NPs receive support from a wide variety of sources, including their district, peers, staff, administrative team, professional networks, governors, parents, family, community, role models, friends and even the former principal of the NP when the NP was a teacher , Osterman and Sullivan 1996, Cheung and Walker 2006, Crow 2007, Kelly and Saunders 2010. Clear district expectations and goals, technical help from supervisors or senior team managements, the capacity of the staff to handle change and mentoring are examples of the type of support given to newly appointed principals.…”
Section: Determinants Affecting the Early Career Stage Of Principalshipmentioning
confidence: 98%
“…Notably, insufficient knowledge in technical managerial competencies has been found to result, to a certain extent, in NPs' inability to revise goals or general alternate strategies (Osterman and Sullivan 1996), a greater tendency to make mistakes, a need to spend an inordinate amount of time on every task, confusion about school budgeting (Nelson et al 2008), high levels of stress (Daresh and Male 2000) and a sense of loneliness (Draper and McMichael 2000) and burnout (Stephenson and Bauer 2010). In contrast, however, there is evidence, although limited in scope, of positive role aspects among NPs, even though they operate within a context of high-stakes accountability and systemic uncertainty.…”
Section: Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite differences in measures of principal self-efficacy the available research indicates that principal self-efficacy is associated with principal well-being and motivation as well as adaptive leadership functioning. Principal self-efficacy has been shown to be positively associated with engagement (Federici and Skaalvik 2011), job satisfaction (Federici and Skaalvik 2012), persistence in pursuing goals (Osterman and Sullivan 1996), motivation for retaining in the principal position (Dimmock and Hattie 1996), the quality of supervision of teachers (Licklider and Niska 1993), collective teacher efficacy (Hallinger et al 2018), and effort to influence teacher attitudes and behaviors (see Hallinger et al 2018). Principal self-efficacy has also been shown to be negatively related to burnout and motivation to leave the principal position (Federici and Skaalvik 2012).…”
Section: Principal Self-efficacymentioning
confidence: 99%
“…Edmonds (1979) contended that the characteristics of an effective school are (1) strong leadership by the principal, especially regarding instructional quality, (2) a pervasive and broadly understood instructional focus; (3) an orderly, safe climate conducive to teaching and learning; (4) teacher behaviors that convey the expectation that all students are expected to obtain at least minimum mastery; and (5) the use of measures of pupil achievement as the basis for program evaluation. Osterman and Sullivan (1994) state that over the last twenty years, efforts to improve the equality of education at the school level have focused on the principal. Leithwood, Begley, and Cousins (1990) believe that highly effective principals demonstrate high levels of commitment to goals for the school.…”
Section: Reform or Restructurementioning
confidence: 99%